2019
DOI: 10.21009/jpeb.007.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Social Interaction, Socio-Economic Status, and Basic Economic Knowledge of Students' Economic Behavior

Abstract: This study aims to determine the effect of social interaction, socioeconomic status, and basic economic knowledge on the economic behavior of MAN students in the Pati Regency. This research uses a quantitative research approach. This study uses primary data obtained from distributing questionnaires to students. The population in this study amounted to 266 students. Participants in this study are 160 students with a proportional random sampling technique. The data analysis technique used is multiple linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…consumption, production, distribution, saving, and investment [8]. S. N. Qomariyah, and S. H. M. Lyn and S. Sahid mentioned that each individual is an economic actor, who will behave economically in his/her daily activities [9][10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…consumption, production, distribution, saving, and investment [8]. S. N. Qomariyah, and S. H. M. Lyn and S. Sahid mentioned that each individual is an economic actor, who will behave economically in his/her daily activities [9][10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the findings of this study confirmed previous findings revealing that the decentralization of fiscal revenues is negatively correlated with income inequality in urban, rural, and rural-urban areas (Chen et al, 2020;Deyin et al, 2017). Qomariyah et al (2019) specifically emphasized that special allocation funds may reduce income inequality. In addition, Su et al (2019) concluded that fiscal decentralization impacted increasing population income and fiscal spending, encouraging income growth for urban and rural residents.…”
Section: Etikonomimentioning
confidence: 99%